In vitro cytotoxicity studies of sixteen plants used for pregnant women’s health conditions in Menoua Division-West Cameroon - Didiane Mefokou Yemele; Bruno Phelix Telefo; Stephanie Chekem Goka; Benoit Telesphore Nguelefack; Pierre Simeon chegaing Fodouop; Richard Simo Tagne; Landry Lienou Lienou; Filomain Nguemo; Paul Fewou Moundipa (International Journal of Phytomedicine, 2015)
In Cameroon, many plants are used in traditional medicine for the treatment of pregnancy and childbirth complaints. However, toxicological potential of most of these plants have not been investigated. In order to evaluate the degree of safety of their users, in vitro cytotoxic potentials of sixteen of these medicinal plants were subjected to the assay using the brine shrimp lethality assay. From this study, the aqueous extract of plant Rauvolfia vomitoria bark was found to be cytotoxic and that of Ageratum conyzoides stem and leaves slightly cytotoxic, with LC50 values of 17.62 and 99.17µg/ml, respectively. The least toxic plant extracts were Aloe buttneri, Commelina benghalensis, Ipomoea tenuirostrisandNelsonia canescens, (LC50 value > 105 µg/ml). Overall fourteen extracts were found to be non-toxic. Most herbal remedies were non cytotoxic but it would be necessary to complete these cyto-toxicological information by mutagenicity, teratogenicity tests as welle as in vivo toxicological tests on animals.